(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Coronary artery bypass grafting has always given advantage over medical management in treating ischaemic heart disease when 5 years survival is concerned. But, surgery is usually avoided in patients with ischaemic cardiomyopathy with low ejection fraction due to perioperative mortality .Here, we are presenting a case of first successfully performed CABG in Bangladedesh in a patient with ejection fraction of 19%. A 58 years old diabetic and hypertensive male patient, having history of myocardial infarction was suffering from ischaemic cardiomyopathy. He presented with compressive central chest pain, dyspnoea and fatigue and was in NYHA functional class IV. His coronary angiogram revealed tripple vessel coronary artery disease and there was severe left ventricular systolic dysfunction on Echocardiography. On 11th June, 2013 he underwent off pump coronary artery bypass graft where 3 grafts were anastomosed on beating heart. There was no peroperative complication and no need for perioperative IABP. Weaning time from ventilation and period of inotropic support were not longer than usual that is required for a patient with normal ejection fraction. Patients postoperative period was unremarkable. After six months follow up, his ejection fraction had improved to 26% and on nine months follow up his ejection fraction was 35%. The patient is apparently symptom less, resumed his job and leading an almost normal life. Therefore, surgery in a skilled hand can combat perioperative mortality and morbidity and gives better result in patient with low ejection fraction. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i3.21036